Hubungan Antara Persepsi Terhadap Harapan Orang Tua, Perfeksionisme, Dengan Fear of Failure Pada Mahasiswa Akhir di Yogyakarta - Dwiyanti, Rezky Naufhal; ama, Roy Gustaf Tupen (Journal of Comprehensive Science, 2025)
This study aims to examine the relationship between perceived parental expectations and perfectionism with fear of failure among final-year university students in Yogyakarta. Academic pressure, high parental expectations, and perfectionistic tendencies are often the dominant factors contributing to students’ fear of failure. A quantitative survey method was employed, involving 231 randomly selected respondents. The instruments included three Likert-type scales: fear of failure (55 items), perceived parental expectations (28 items), and perfectionism (33 items). Pearson correlation analysis revealed a positive and significant relationship between perceived parental expectations and fear of failure (r = 0.662; p < 0.05), as well as between perfectionism and fear of failure (r = 0.698; p < 0.05). Multiple linear regression analysis indicated that the two independent variables jointly accounted for 64.5% of the variation in fear of failure (R² = 0.645). These findings highlight the importance of supportive parenting and psychological interventions to reduce maladaptive perfectionism and promote student well-being.